2017
DOI: 10.1016/j.yexcr.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoic acid signaling on extraocular muscle myogenic precursor cells in vitro

Abstract: One major difference between limb and extraocular muscles (EOM) is the presence of an enriched population of Pitx2-positive myogenic precursor cells in EOM compared to limb muscle. We hypothesize that retinoic acid regulates Pitx2 expression in EOM myogenic precursor cells and that its effects would differ in leg muscle. The two muscle groups expressed differential retinoic acid receptor (RAR) and retinoid X receptor (RXR) levels. RXR co-localized with the Pitx2-positive cells but not with those expressing Pax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Exogenous RA (bead implantation) in chick embryos impacts the expression of the myogenic markers Pitx2 and Tbx1 (Bothe et al, 2011). Furthermore, Retinoid X receptor (RXR) co-localizes with PITX2 in extraocular muscle cells (Hebert et al, 2017). Together with our results, this clearly shows that perturbed RA signaling results in downregulation of Pitx2 in BA1 and BA2, which in turn results in branchiomeric muscle defects.…”
Section: Diverse Reactions Of Muscle Precursor Cells To Ra Signalingsupporting
confidence: 73%
“…Exogenous RA (bead implantation) in chick embryos impacts the expression of the myogenic markers Pitx2 and Tbx1 (Bothe et al, 2011). Furthermore, Retinoid X receptor (RXR) co-localizes with PITX2 in extraocular muscle cells (Hebert et al, 2017). Together with our results, this clearly shows that perturbed RA signaling results in downregulation of Pitx2 in BA1 and BA2, which in turn results in branchiomeric muscle defects.…”
Section: Diverse Reactions Of Muscle Precursor Cells To Ra Signalingsupporting
confidence: 73%
“…Consistently, in the present study, our results demonstrated that administration of bexarotene significantly increased the RXR/PPARγ interaction, and upregulated the expression of SIRT6, while downregulating the pro-inflammatory cytokines including IL-1β, IL-6, and TNF-α at 24 h after SAH. UVI3003, a selective RXR antagonist [32, 47, 48], could ultimately prevent the beneficial effects of RXR activation in retinal degenerations [49]. Similarly, when we inhibited RXR using UVI3003 or knockdown RXR before SAH induction, the effects of bexarotene treatment on PPARγ/SIRT6 upregulation and neuroinflammation suppression as well as neurological deficit improvement were abolished at 24 h after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mice heterozygous for the Pitx2 null allele and those in which the Pitx2 knockout was limited to NC cells were viable and displayed corneal, iris, and scleral defects similar to ARS in humans ( Chen and Gage, 2016 ). Retinoic acid is a known regulator of Pitx2 expression ( Bohnsack et al, 2012 ; Williams and Bohnsack, 2015 ; Chawla et al, 2016 ; Hebert et al, 2017 ; Draut et al, 2019 ; Williams and Bohnsack, 2019 ), but has differential effects depending on embryonic stage. During the early stages, retinoic acid decreases Pitx2 expression within NC cells migrating toward the pharyngeal arches.…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%